Vaganačka pećina (In situ, 2024)
In May 2023, archaeological excavation of Vaganačka pećina (Vaganačka cave) on the coastal side of southern Velebit was carried out, with the aim of approaching the site after almost 40 years, using modern research methods in order to collect data that were not available before. Two trial trenches have been opened, which for now suggest a dual use of space in the cave: a residential part and a part for animal stabling. For now, this assumption refers only to the Bronze Age period, while for older periods it is only certain that the cave was used to for animal stabling.
Keywords: Velebit; Vaganačka pećina; prehistory